Reviewing the Standards for protection of Geographical Indications in Tanzania: A case of Kyela Rice - NDUNGURU, ADRIAN; Haule, Romuald; Mwanga, Elia (International Journal of Business, Management and Economics, 2024)
This paper examines the standards for effective protection of Geographical Indications in Tanzania. The Trade-Related Aspects of Intellectual Property Rights Agreement (herein after the TRIPS Agreement) provides for obligations of state parties to the Agreement to protect intellectual property rights in their respective countries. However, the TRIPS Agreement does not specifically state the conditions or standards for the protection of geographical indications. This paper reviewed various legal instruments to establish the essential standards that can be adopted to protect geographical indications of Kyela Rice. The methodology used to collect data is documentary review and data are analyzed using content analysis.